USING ENGLISHLEAP WEBSITE IN TEACHING VOCABULARY: A STUDY AT MADANI ALAUDDIN PAOPAO - Andi Winda Lestari; Nur Aliyah Nur (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
This paper aims at describing whether Englishleap website is effective in improving students’ vocabulary mastery or not. The researcher applied quasi experimental design. The population of this research was the tenth grade students of MA Madani Alauddin Paopao which consisted of 128 students. The researcher took 16 students in experimental class and 16 students in control class. The independent variable of this research was Englishleap website and the dependent variable of this research was Students’ vocabulary mastery. The instrument of this research was a written test used in pre-test and post-test. The result of the data indicated that there was a significant difference between students’ post-test in experimental class and controlled class. The mean score of post-test (91.25) in experimental class was higher than the mean score of post-test (71.87) in controlled class. From t-test, the researcher found that the value of the t-test (3.93) was higher than t-table (2.043) at the level of significance 0.05 with degree of freedom (df)= 32. From the result of the research the researcher concluded that the hypothesis was accepted. It means that using Englishleap website was effective in improving students’ vocabulary mastery at the tenth grade students of MA Madani Alauddin Paopao. Therefore, English teacher may use the Englishleap website in teaching process, because it can make the learning process more enjoyable, fun and effective.